PENGEMBANGAN MEDIA KOMIK DIGITAL BERSUARA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN KELAS IV SDN PANCORAN 07 PAGI - Lestari, Citra; Sulistyani Puteri Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The rapid growth of technology has significantly impacted various fields, especially field of education. In this case, technology can be used to create fun, interactive, digital learning media or teaching aids that are aligned with the Merdeka Curriculum. In this curriculum, Bahasa Indonesia learning requires students to understand fictional texts in order to comprehend, identify ideas, and interpret information from the texts they read or listened to. Based on analysis and observation at SDN Pancoran 07 South Jakarta, there is a need for make learning media to help students understand and interpret information from reading materials. Therefore, a digital comic with voiceover in Indonesian was developed on the topic of “Pertukaran dan Pembayaran” , using the ADDIE development model adjusted to its five stages. The goal of developing this digital comic media is to improve reading comprehension skills for 4th-grade students. The results of the research show that using the digital comic media has led to an improvement in reading comprehension, which can be seen from the pre-test and post-test results conducted in each class. Specifically, in the media field test, an improvement of 63.5% was observed.